Analisis Kebutuhan Pengembangan Media Big Book Untuk Pembelajaran Karakter Disiplin Anak Usia Dini - Rafika Sita Camalia; Purwati Purwati; Anggi Maulana Rizqi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Discipline is a fundamental character value that should be fostered from early childhood; however, its implementation in Early Childhood Education (ECE) remains constrained by the limited availability of instructional media specifically designed to support character development. This study aimed to analyze the need for developing a Direct Instruction-based Big Book as a foundation for designing instructional media to strengthen disciplinary character in young children. A descriptive qualitative approach was employed, with data collected through classroom observations and semi-structured interviews involving Group B teachers at a kindergarten in Tasikmalaya City, Indonesia. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that children's disciplinary character has generally developed but remains inconsistent due to differences in family support and the intensity of teacher supervision. Furthermore, the instructional media currently used are general in nature and have not been specifically designed to facilitate discipline character education. Teachers expressed the need for engaging, contextual, structured, and developmentally appropriate visual learning media. The scientific contribution of this study lies in providing an empirical needs analysis that serves as a foundation for developing a Direct Instruction-based Big Book, thereby extending previous studies that primarily focused on media implementation rather than systematic needs assessment. These findings imply that instructional media development for early childhood education should be grounded in teachers' actual needs to produce more relevant learning resources, strengthen systematic classroom practices, and enhance the effectiveness of discipline character education